Gold Coast Mission History 1471-1880 - Bowers, J.O. (DMNE WORD PUBLICATIONS, TECHNY, ILLINOIS, U.S.A., 1956)
The Gold Coast, a member of the British Commonwealth of Nations, is politically foremost of all Commonwealth Colonial territories in tropical Africa. Situated on the Gulf of Guinea, it is bounded by that gulf on the south, on the east by Togoland under French trusteeship, on the north by Haute Volta and on the west by the Ivory Coast. The total area is approximately 91,843 square miles, slightly larger than that of Great Britain. This includes the Colony along the coast, Ashanti, the Northern Territories and a narrow strip of Togoland, held by the British under Mandate from the League of Nations since 1919 and placed under Trusteeship in 1946. The 334 miles of coast consist generally of a low sandy foreshore on which the Atlantic swell breaks almost unceasingly. As for the people along the coast, they are divided into twenty-one states, passing from west to east: Western Nzima, Eastern Nzima, Upper and Lower Axim, Upper and Lower Dixcove, Ahanta, Dutch and English Sekondi, Shama, Komenda, Edina, Ogua, Nkusukum, Anomabu, Ebiram, Winneba, Gomoa Asen, Ga, Prarnpram and Ada. Many of these divisions have been introduced as a result ( of European settlements on the coast, there being only fourteen states in the j: seventeenth and eighteenth centuries, and perhaps already that many in 1471 L when the Portuguese arrived.
Heritage Material
Keywords: Mission; History; Gold Coast; Commonwealth of Nations; Colonialism